Penerapan Konsep Pembelajaran MIPA Topik Usaha dan Energi: Studi Pustaka - Minerva Anindyta; Fajar Sodik; Nurzeini Herdiansyah; Muhamad Sofiandi; Rina Hidayati Pratiwi (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Work and energy are important topics in physics learning. Learning on this topic can be done using various methods and media, which provide different results depending on the approach used. This study aims to identify various learning models and media and their influence on learning about work and energy through a meta-analysis of 17 relevant research journals. The results of the study indicate that there are various learning methods that can be applied, including the 7E Learning Cycle, STEM, Problem Solving, Think-Pair-Share, Inquiry, and others. Of these various methods, the inquiry approach is the most widely used because it is relevant to the student-based curriculum that positions teachers as facilitators in developing students' thinking skills and intellectual discipline.